In Vitro and In Vivo Activities of Zinc Linolenate, a Selective Antibacterial Agent against Helicobacter pylori - Huang, Yanqiang (Antimicrob Agents Chemother, 2019)
Helicobacter pylori is a major global pathogen, and its infection represents a key factor in the etiology of various gastric diseases, including gastritis, peptic ulcers, and gastric carcinoma. The efficacy of current standard treatment for H. pylori infection including two broad-spectrum antibiotics is compromised by toxicity toward the gut microbiota and the development of drug resistance, which will likely only be resolved through novel and selective antibacterial strategies. Here, we synthesized a small molecule, zinc linolenate (ZnLla), and investigated its therapeutic potential for the treatment of H. pylori infection. ZnLla showed effective antibacterial activity against standard strains and drug-resistant clinical isolates of H. pylori in vitro with no development of resistance during continuous serial passaging. The mechanisms of ZnLla action against H. pylori involved the disruption of bacterial cell membranes and generation of reactive oxygen species. In mouse models of multidrug-resistant H. pylori infection, ZnLla showed in vivo killing efficacy comparable and superior to the triple therapy approach when use as a monotherapy and a combined therapy with omeprazole, respectively. Moreover, ZnLla treatment induces negligible toxicity against normal tissues and causes minimal effects on both the diversity and composition of the murine gut microbiota. Thus, the high degree of selectivity of ZnLla for H. pylori provides an attractive candidate for novel targeted anti-H. pylori treatment.